Swirl flow bioreactor containing dendritic copper-containing alginate beads: A potential rapid method for the eradication of Escherichia coli from waste water streams. (April 2015) - Thomas, Simon F.; Rooks, Paul; Rudin, Fabian; Cagney, Neil; Balabani, Stavroula; Atkinson, Sov; Goddard, Paul; Bransgrove, Rachel M.; Mason, Paul T.; Allen, Michael J.
Abstract: Despite the increasing use of Decentralised Waste Water Systems (DEWATS) in the developing world, which effectively dewater sludge, the problem of preventing the pathogen-laden water produced by these systems from re-entering the food chain constitutes a continuing burden on developing countries, which hinders subsequent advancements. We report on a swirl flow reactor generating high mixing areas which in conjunction with Cu/alginate beads effectively reduces Escherichia coli numbers by five orders of magnitude in 10 min. The system is simple, low cost, portable and modular; it can be assembled with simple plastic plumbing parts available in most areas and, once further developed, may represent a useful adjunct for both existing and new DEWATS facilities.